Highlight article: Early activation of ubiquitin-proteasome system at the diaphragm tissue occurs independently of left ventricular dysfunction in SHR rats. Issue 3 (February 2020) - Souza, Pamella Ramona Moraes de; da Palma, Renata Kelly; Vieira, Rodolfo Paula; Santos, Fernando dos; Monteiro-De-Moraes, Wilson Max Almeida; Medeiros, Alessandra; Koike, Marcia Kiyomi; Arantes-Costa, Fernanda Magalhães; De Angelis, Kátia; Irigoyen, Maria Claudia; Consolim Colombo, Fernanda Marciano
Hypertensive status induces modifications in the respiratory profile. Previous studies have indicated that hypertensive rats show increased respiratory-sympathetic coupling compared to normotensive rats. However, these effects and especially the mechanisms underlying such effects are not well known. Thus, we evaluated the influence of high blood pressure and autonomic dysfunction on a ventilatory pattern associated with lung injury and on the ubiquitin-proteasome system of the diaphragm muscle. Autonomic cardiovascular modulation (systolic BP variance and low-frequency band and pulse interval variance) and arterial blood gases patterns (pH, pO2, HCO3, SpO2 ), can be changed by hypertension, as well exacerbated chemoreflex pressor response. We observed that the diaphragm muscle of SHR showed increase in type I cross-sectional fiber (16%) and reduction in type II cross-sectional fiber area (41%), increased activity of the ubiquitin-proteasome system and lipid peroxidation, with no differences between groups in the analysis of ubiquitinated proteins and misfolded proteins. Our results showed that hypertension induced functional compensatory/adverse alterations associated with diaphragm fiber type changes and protein degradation as well as changed autonomic control of circulation. In conclusion, we believe there is an adaptation in ventilatory pattern in regarding to prevent the development of fatigue and muscle weakness and improve ventilatory endurance. Impact statement: It was well known that hypertension can be driven by increased sympathetic activity and has been documented as a central link between autonomic dysfunction and alterations in the respiratory pattern. Our study demonstrated the impact of hypertension in ventilatory mechanics and their relationship with diaphragm muscle protein degradation. These findings may assist us in future alternative treatments to prevent diaphragm fatigue and weakness in hypertensive patients.